2020
DOI: 10.1063/5.0014006
|View full text |Cite
|
Sign up to set email alerts
|

The bond dissociation energy of VO measured by resonant three-photon ionization spectroscopy

Abstract: The predissociation threshold of VO has been measured using resonant three-photon ionization (R3PI) spectroscopy. Given the high density of electronic states in the molecule, it is argued that the molecule dissociates rapidly as soon as the thermochemical bond dissociation energy (BDE) is exceeded, allowing the measured predissociation threshold to be assigned as the BDE. This is the first time a BDE has been measured using the R3PI method. The first photon is provided by an optical parametric oscillator (OPO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…Theoretical values of D 0 (NiO + ) ,, and D 0 (NiS + ) , are all systematically lower than these experimentally measured values. It is worth noting the suggested trend in oxide ,, and sulfide , D 0 values for Ni + is identical with that for Sc + , Ti + , V + , Cr + Mn + , Fe + , and Co + but opposite Cu + and Zn + . While the photodissociation spectrum of NiO + has not previously been measured, Hettich et al recorded the spectrum of NiS + from 230 to 480 nm using an arc lamp and monochromator with 10 nm resolution.…”
Section: Introductionsupporting
confidence: 59%
“…Theoretical values of D 0 (NiO + ) ,, and D 0 (NiS + ) , are all systematically lower than these experimentally measured values. It is worth noting the suggested trend in oxide ,, and sulfide , D 0 values for Ni + is identical with that for Sc + , Ti + , V + , Cr + Mn + , Fe + , and Co + but opposite Cu + and Zn + . While the photodissociation spectrum of NiO + has not previously been measured, Hettich et al recorded the spectrum of NiS + from 230 to 480 nm using an arc lamp and monochromator with 10 nm resolution.…”
Section: Introductionsupporting
confidence: 59%
“…It can be seen from Figure 1 a that upon IR irradiation at 1030 cm −1 , both C 60 VO + and C 60 V + (H 2 O) decrease in intensity. For C 60 VO + , since VO + has a large binding energy of 584 kJ mol −1 , [17] the most plausible infrared induced dissociation channel is C 60 VO + →C 60 +VO + with a calculated dissociation energy of 254 kJ mol −1 . For C 60 V + (H 2 O), the naturally anticipated dissociation channels include truenormalC60normalV+(H2O)normalC60normalV++normalH2normalO truenormalC60normalV+(H2O)normalC60+normalV+(H2O) …”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we have demonstrated that for small d- and f-block molecules, the high density of electronic states in the vicinity of the ground separated fragment limit allows the molecule to dissociate via spin–orbit and nonadiabatic couplings as soon as this limit is exceeded in energy, leading to a sharp drop in the ion signal obtained in a resonant two-photon ionization (R2PI) spectroscopy experiment. As illustrated in Figures and S1–S5, this method has allowed us to measure the predissociation thresholds of ScB 2 , TiB 2 , VB 2 , YB 2 , and MoB 2 .…”
mentioning
confidence: 99%